Overview and GNC design of the CubeSat Proximity Operations Demonstration (CPOD) mission. (December 2018) - Roscoe, Christopher W.T.; Westphal, Jason J.; Mosleh, Ehson
Abstract: The CubeSat Proximity Operations Demonstration (CPOD) mission will demonstrate rendezvous, proximity operations, and docking with a pair of 3U CubeSats using miniaturized components and sensors. The goal of this mission is to develop small spacecraft technologies with game-changing potential and validate these technologies via spaceflight. Several new systems have been designed specifically for this program, including: next generation star trackers, next generation miniature reaction wheels, miniature cold-gas multi-thruster propulsion modules, a new relative navigation sensor suite, power management and distribution electronics based on flight proven designs, and intelligent software solutions hosted on multiple low-power Linux ARM processors. This paper will present an overview of the CPOD spacecraft and the mission Concept of Operations, as well as the design of the formation flying guidance, navigation, and control subsystem and algorithms. Highlights: Design of GNC algorithms for small satellite rendezvous, proximity operations (RPO). Overview of the NASA CubeSat Proximity Operations Demonstration (CPOD) mission. Passively safe RPO based on lessons learned from DART, Orbital Express, and Prisma. Fuel-optimal n-impulse J2 maneuver targeting using differential orbital elements. Monte Carlo end-to-end mission simulation testing for validation.